Clinicopathological and molecular features of tubo-ovarian carcinosarcomas: a series of 51 cases - Liang, Fan; Shi, Yue; Chen, Yiqing; Tao, Xiang; Ding, Jingxin (Frontiers in Oncology, 2024)
Objective: Tubo-ovarian carcinosarcomas are rare, extremely aggressive malignant tumors that contain both carcinomatous and sarcomatous components. Due to the disease's rarity, developing an effective treatment strategy for ovarian carcinosarcomas has been challenging. A study was conducted to investigate the clinicopathologic and molecular features of this rare disease.We enrolled all patients diagnosed with Tubo-ovarian carcinosarcomas from January 2007 to December 2022. The clinical and pathological data were gathered from medical records.Kaplan-Meier curves were plotted to calculate OS and PFS. Log-rank test and cox regression model were utilized to explore the relationship between clinicopathological parameters and survival.Patients with cancer tissues available had sequencing with 242-gene-panel done to investigate the mutational landscape and signature of the disease.Results: 65% of the patients were diagnosed at advanced-stage cancer. The median PFS and OS of this cohort were 27 and 40 months, respectively and there was no significant difference in survival between the homologous and heterologous components in sarcoma. Unexpectedly, staging seemed not have effects on prognosis. All patients had surgical attempts and suboptimal debulking status was correlated with poorer PFS and OS. MSI was identified in 0% with low TMB indicated poor response of immunotherapy. Low Her-2 expression is controversial to previous reports and gave us limited choices with this rare and aggressive disease. We surprisingly found the HRD-positive status was identified in 64% of OCS, which is significantly higher than UCS and other types of epithelial ovarian cancer. The fact that all patients in our cohort received Olaparib as maintenance therapy had survived over 30 months and two had no evidence of recurrence at the latest follow-up might further validate the role of PARPi in the management of OCS.OCS patients seemed to respond to Carboplatin/paclitaxel with optimal PFS and OS.Cytoreduction with no residual was proved to be the sole independent prognostic factor. WES should be done to assess the prognosis and assist with the target therapy, especially HRD test might help select potential patients benefit from PARPi.